Thyroid Hemiagenesis: An Incidental Discovery during Treatment for Papillary Thyroid Carcinoma - Chang Haur Lee; Yazid Pol Ong; Firdaus Hayati; Muhammad Zahid Abdul Muien; Siti Zubaidah Sharif (Journal of Medical Ultrasound)
Thyroid hemiagenesis (THA) is a rare congenital abnormality in which one of the thyroid lobes fails to develop normally. The prevalence rates range from 0.02% to 0.25%, with no gender preponderance and most commonly involve the left lobe. We report a case of left THA in a 37-year-old female that was found incidentally during total thyroidectomy for right papillary thyroid carcinoma. Most patients with THA are asymptomatic, however, may have subclinically raised thyroid-stimulating hormone levels or be predisposed to developing thyroid disorders such as nodular goiter, hyperthyroidism, Grave’s disease, Hashimoto’s thyroiditis, hyperparathyroidism, or malignancy. Usual imaging techniques such as ultrasonography, computed tomography, and magnetic resonance imaging allow the confirmation of diagnosis and provide clearer glandular and regional visualization. Additional modalities such as thyroid scintigraphy enable the functional assessment and identification of any suspicious nodules and aid in decision-making. THA is a very uncommon condition and the diagnosis is primarily made through imaging. Clinicians should be aware that this condition exists along with documented associations of concomitant thyroid disorders and malignancy.